Pengaruh listing age, leverage, opini audit terhadap kinerja keuangan dengan reputasi KAP sebagai variabel moderasi - Neuneu Supri Antini (LPMP Imperium, 2024)
This research aims to examine and determine the influence of listing age, leverage and audit opinion on financial performance with KAP reputation as a moderating variable. This research is quantitative research with financial performance as the dependent variable. Financial performance in this research is measured by ROA. The population in this study are financial industry companies listed on the Indonesia Stock Exchange for the 2022-2023 period which were downloaded from the Indonesia Stock Exchange website (www.idx.co.id) and the company's official website. The population was filtered using a purposive sampling technique with the aim that the data obtained would be more representative so that the sample in this study was 105 companies that met the predetermined criteria. The research results show that the listing age and leverage variables have an effect on financial performance, while the audit opinion variable has no effect on financial performance. Furthermore, if we look at the moderating variables, then all dependent variables can influence the dependent variable. So it can also be concluded that the reputation of a public accounting firm (KAP) can strengthen the influence of the variables listing age, leverage and audit opinion on financial performance.